Biomarkers of interstitial lung disease in systemic scleroderma and their significance - D. V. Khorolsky; A. A. Klimenko; A. A. Kondrashov; N. A. Shostak; N. A. Demidova (Klinicist)
Systemic scleroderma (SSD) is a rare immune-inflammatory systemic disease of connective tissue with a typical lesion of skin, blood vessels, musculoskeletal system and internal organs (lungs, heart, digestive tract, kidneys). The SSD pathogenesis is based on activation of a cascade of complex immune interactions that lead to vasculopathy. The presence of many pathophysiological links in the progression of the disease causes a variety of clinical manifestations in various patients with SSD. A full assessment of all stages of SSD development is still being carried out and every newly open element of the interaction of immunological subjects completes the overall picture of the disease. A number of studies show a correlation between level of several biomarkers and both disease prognosis and estimated therapy effectiveness. Recent data confirm importance of the biomarkers for formation of patterns of a particular disease phenotype in a specific patient. Depending on relation of the biomarkers to various biological processes, several of their categories are distinguished: biomarkers expressed in lung tissue, cellular units of immunity, nucleic acids, acute phase indicators, connective tissue growth factors, matrix proteinases and their inhibitors, chemokines and cytokines, as well as biomarkers of endothelial activation. Discovery of a novel set of the indicators can be decisive in determining the management tactics and forecasting the response to therapy of some groups of patients with SSD. By combining the most recent data on significant markers obtained in the framework of extensive studies, we have described the most significant biomarkers of SSD and their link to interstitial lung disease (ILD) that is formed in SSD.